Genetic predisposition for chronic venous insufficiency in several genes for matrix metalloproteinases (MMP-2, MMP-9, MMP-12) and their inhibitor TIMP-2 - Slonková, V; Slonková, V; Vašků, A; Vašků, V (Journal of the European Academy of Dermatology and Venereology, 2017)
OBJECTIVE: The project was scheduled as a case-control study to investigate the correlation between MMP-2 (rs243864), MMP-9 (3918242), MMP-12 (rs7123600) and TIMP-2 (rs8176329) polymorphisms and chronic venous disease (CVD) risk. The genotype and phenotype research envisages the testing of possible associations between MMP and TIMP-2 genotypes and phenotypes of CVD. MATERIAL AND METHODS: 150 patients with CVD and 227 controls were enrolled into the study. The MMPs and TIMP-2 genotypes were identified by the PCR method and restriction analysis according to standard protocols. RESULTS: The G allele of MMP-2 -790 T/G was 1.85 times more frequent in men with CVD than in the control group (P = 0.008). The T allele of MMP-9 -1562 C/T was observed 2.571 times more frequently in patients with CVD than in the control individuals (both in men and women) with clinically significant specificity (P = 0.0000009). The G allele of MMP-12 rs7123600 was determined 2.082 times more frequently in female patients with CVD than in the control group with clinically significant specificity (P = 0.02). No significant result in TIMP-2 rs8176329 polymorphism in the case-control study was observed. CVD women with G allele in MMP-2 -790 T/G in the genotype-phenotype study are seen to develop ulceration 2.539 times more frequently (P = 0.003). The G allele of MMP-12 rs7123600 was detected 3.167 times more frequently in CVD women with ulceration compared with CVD women without ulceration (P = 0.007). In CVD men in C6 stage, the incidence of AG genotype in rs7123600 MMP-12 polymorphism was found to be 4.675 times higher compared to CVD women with C6 staging (P = 0.005). The AG genotype in TIMP 2 rs8176329 polymorphism was found to be associated with higher risk of tumour (P = 0.01). CONCLUSION: Studying these polymorphisms can contribute to better identification of patients at higher risk of developing CVD, while providing the most appropriate prevention and treatment strategies for limiting the progression and complications of CVD.
Keywords: dospělí; senioři nad 80 let; studie případů a kontrol; matrixové metaloproteinasy; Matrix Metalloproteinases; Humans; Polymerase Chain Reaction; Genetic Predisposition to Disease; genetická predispozice k nemoci; lidé středního věku; Middle Aged; Aged, 80 and over; Genotype; Young Adult; Chronic Disease; mladý dospělý; Phenotype; Tissue Inhibitor of Metalloproteinase-2; mužské pohlaví; Adult; žilní insuficience; tkáňový inhibitor metaloproteinasy 2; Disease Progression; polymerázová řetězová reakce; fenotyp; chronická nemoc; ženské pohlaví; genotyp; lidé; Case-Control Studies; Aged; Venous Insufficiency; senioři; progrese nemoci; Male; Female